Adaptation of three mulberry (Morus spp.) varieties in Hidalgo State - Rodríguez-Ortega Alejandro; Martínez-Menchaca Aarón; Ventura-Maza, Alejandro; Vargas-Monter, Jorge (Revista Mexicana de Ciencias Agrícolas, 2018)
The objective of this paper was to evaluate the adaptation of three varieties of mulberry in the regions of Valle del Mezquital, Huasteca and Otomí-Tepehua, Hidalgo State, established in early October, 2010, for the promotion of sericulture. We used a completely randomized design with factorial arrangement 3 (region) x 3 (variety). The information was recorded from 35 plants per variety during 6 months of study. The variables analyzed were: survival rate, plant vigor, pest and disease incidence, height, number of buds, number of branches, and number of leaves per plant and leaf area. ANOVA and mean comparison were performed, finding survival rates above 95% in the three regions studied (p> 0.05). SLP5 variety in the region Otomí-Tepehua (p> 0.05), had the lowest survival rate (89%). The plant vigor was lower in Valle del Mezquital and the variety SLP5. The final height of the plants was differed between regions; Otomí-Tepehua (67.7 cm), Huasteca (63 cm) and Valle del Mezquital (44.7 cm). SLP5 and SLP3 varieties showed higher height (p> 0.05). In the Valle del Mezquital region and, the SLP5 variety the largest bud issue was registered. The variety SLP3 and Kamva had a higher number of branches, leaves and leaf area in the Huasteca and Otomí-Tepehua regions, while the SLP5 variety presented small leaves and was susceptible to diseases. We conclude that it is feasible to establish the SLP3 and Kamva varieties for its high adaptability to the three regions of Hidalgo State.